Acrylate grouting material for impervious repair of concrete cracks and preparation method of acrylate grouting material
By mixing acrylate, water, crosslinking agent and accelerator, combining modified styrene-acrylic emulsion and modified talc powder, acrylate grouting materials were prepared, which solved the short service life of existing materials, poor anti-seepage performance and cured substances. The problem of large volume shrinkage achieves higher anti-seepage performance, anti-drying shrinkage performance and service life.
Patent Information
- Application Number
- CN202411662644.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-14
AI Technical Summary
The existing acrylate grouting materials have problems such as short service life, poor anti-seepage performance and large shrinkage of cured objects.
Component A is obtained by mixing 15-25 parts by mass of acrylate, 50-60 parts by mass of water, 20-30 parts by mass of crosslinking agent and 0.5-2 parts by mass of accelerator; 50-60 parts by mass of mass of accelerator were obtained; The modified styrene acrylic emulsion, 40-50 parts by mass of water, 1-3 parts by mass of initiator and 1-5 parts by mass of modified talc powder, to obtain component B; then component A and component B are mixed Blend to prepare acrylate grouting material.
It improves the anti-seepage, anti-drying and shrinkage properties and service life of acrylate grouting materials, and enhances the compressive strength and durability of the materials.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to an acrylate grouting material for concrete crack anti-seepage repair and a preparation method thereof. Background Art
[0002] The application of concrete in engineering construction has a long history. With the advancement of urbanization in my country, a large number of concrete buildings have sprung up in my country. However, due to the large expansion and contraction of concrete and its susceptibility to climate change, various types of cracks have appeared in some concrete projects that have been built in my country. The existence of cracks has brought about various water leakage problems. Water leakage not only affects the use environment of the building, but also damages the building structure and reduces durability. Concrete seepage and leakage is a common problem in civil engineering and water conservancy projects. Grouting can improve the impermeability and overall safety of the concrete of the injected building, improve the internal conditions, and play a role in anti-seepage, reinforcement, and water blocking. Grouting is also a good way to solve such problems. Choosing suitable anti-seepage repair materials is crucial to the treatment of water leakage in concrete projects.
[0003] Traditional grouting materials have poor plugging effects and complex construction, which seriously affects the anti-seepage repair effect. In addition, ordinary cement slurry can generally only plug pores and cracks larger than 0.2 mm in size. It takes a long time to solidify and is easily washed away by water flow, resulting in poor plugging effects. Acrylate grouting materials have the advantages of low viscosity, easy injection into micro-cracks, controllable gel time, low permeability coefficient, and high water absorption and expansion rate. They are very suitable for anti-seepage repair of micro-cracks in underground projects. However, the gel speed and gel effect of acrylate grouting materials are easily affected by water dilution, and they are prone to water loss and shrinkage in a dry environment, which affects the plugging effect on the leakage water channel. Therefore, it is crucial to develop an anti-seepage repair grouting material with good anti-seepage performance, small volume shrinkage in a dry environment, and long service life. Summary of the invention
[0004] The purpose of the present invention is to provide an acrylate grouting material for concrete crack anti-seepage repair and a preparation method thereof, so as to solve the following technical problems: Existing acrylate grouting materials have the problems of short service life, poor anti-seepage performance and large volume shrinkage of the cured product.
[0005] The purpose of the present invention can be achieved by the following technical solutions: A method for preparing an acrylic acid salt grouting material for concrete crack anti-seepage repair, characterized in that it comprises at least the following preparation steps: Mix 15-25 parts by weight of acrylate and 50-60 parts by weight of water, add 20-30 parts by weight of a crosslinking agent and 0.5-2 parts by weight of an accelerator and disperse them evenly to obtain component A; Disperse 50-60 parts by weight of modified styrene-acrylic emulsion, 40-50 parts by weight of water, 1-3 parts by weight of initiator, and 1-5 parts by weight of modified talc powder to obtain component B; The component A and the component B are blended to obtain an acrylate grouting material.
[0006] As a further solution of the present invention: the preparation method of the modified styrene-acrylic emulsion comprises the following steps: The water-based epoxy emulsion and the curing agent are evenly mixed, and the styrene-acrylic emulsion is added, and dispersed for 5-10 minutes at a high-speed dispersion shearing machine of 1000-1500 r / min to obtain a modified styrene-acrylic emulsion.
[0007] As a further solution of the present invention: the curing agent is an aziridine cross-linking agent, and the mass ratio of the water-based epoxy resin, the curing agent and the styrene-acrylic emulsion is 1:0.5-3:1-6.
[0008] As a further solution of the present invention: the preparation method of the modified talc powder comprises the following steps: The talc powder is soaked in an acetic acid solution with a pH of 4-5, filtered, and then dried in a vacuum oven at 110-130° C. to obtain an acid-modified talc powder; The acid-modified talc powder is added to a titanate coupling agent, filtered, and then dried in a vacuum oven at 110-130° C. to obtain a surface-modified talc powder; The surface modified talc powder is added into a high-speed mixer, stirred at high speed and heated, and when the temperature reaches 95-105° C., stearic acid is added, stirred at high speed and kept warm for 6-10 minutes to obtain modified talc powder.
[0009] As a further solution of the present invention: the particle size of the talc powder is 4-10 μm, the mass ratio of the acid-modified talc powder to the titanate coupling agent is 1:0.05-0.2, and the mass ratio of the surface-modified talc powder to the stearic acid is 1:0.05-0.1.
[0010] As a further solution of the present invention: the acrylate is any one or more mixtures of calcium acrylate, sodium acrylate or magnesium acrylate, and the crosslinking agent is any one or more mixtures of polyethylene glycol allyl ether, polyethylene glycol acrylate, hydroxyethyl acrylate or hydroxyethyl methacrylate.
[0011] As a further embodiment of the present invention: the accelerator is a mixture of any one or more of triethanolamine, diethanolamine, ferrous sulfate or sodium thiosulfate, and the initiator is a mixture of any one or more of potassium persulfate, ammonium persulfate, sodium persulfate or methyl ethyl ketone peroxide.
[0012] An acrylate grouting material for concrete crack anti-seepage repair is prepared by any one of the above preparation methods.
[0013] Beneficial effects of the present invention: The acrylate grouting material for the anti-seepage repair of concrete cracks prepared in this application is a two-component slurry. The A and B components are evenly mixed, and a free radical polymerization reaction occurs. The acrylate grouting material is poured into the stratum or cracks to fill the cracks, improve the stratum strength, and reduce the permeability. Component A is an acrylate slurry, which is a hydrosol composed of acrylate monomers, crosslinking agents, and promoters. After the reaction, a water-insoluble polymer is generated. The slurry has the advantages of low viscosity, can be injected into small cracks, controllable gel time, and small permeability coefficient. Component B includes a mixed emulsion composed of modified styrene-acrylic emulsion, an initiator, and modified talcum powder. The present application utilizes modified styrene-acrylic emulsion to effectively improve the problem of volume loss and shrinkage of the material, improve the compressive strength and anti-seepage ability of the material, and also utilizes modified talcum powder to reduce the shrinkage of polymer foam and enhance the durability of the material. The acrylate grouting material for the anti-seepage repair of concrete cracks prepared in this application is low in price and can be widely used in tunnels, dams, culverts, and anti-seepage and plugging of concrete seepage cracks.
[0014] Modified styrene-acrylic emulsion is introduced in the present application. As a water-soluble polymer emulsion, styrene-acrylic emulsion has good compatibility with concrete. When it is added to acrylate slurry, the slurry solid content can be increased, so that it has a lower volume shrinkage rate and reduces the risk of repeated leakage. A large amount of hydroxyls are contained in styrene-acrylic emulsion. When acrylate undergoes polymerization reaction, the hydroxyls in styrene-acrylic emulsion are cross-linked with the gel network structure in the form of hydrogen bonds to form a secondary cross-linked network. The secondary cross-linked network strengthens the network structure of the gel, plays a filling role in the gel, reduces the pore diameter of the internal pores of the gel, increases the gel solid content, and improves the overall compactness. Simultaneously, the secondary cross-linked network strengthens the interaction between the molecular chains, and the binding force of the gel network molecular chain increases. The network expansion during water absorption and swelling is greatly restricted, and it becomes difficult for water molecules to pass through the gel network, thereby reducing the permeability coefficient of the grouting material, improving the impermeability, limiting the entry and diffusion of water molecules, and also reducing the dry volume shrinkage of the grouting material. The present application also utilizes water-based epoxy resin to blend and modify styrene acrylic emulsion. The epoxy resin has low curing shrinkage and good water retention, which further reduces the shrinkage of the grouting material. After curing, the epoxy emulsion contains more polar groups such as epoxy groups, hydroxyl groups, and ether bonds, and has higher adhesion. In addition, the cured epoxy resin presents a three-dimensional network structure with a large cross-linking density and a relatively tight molecular structure. It has good chemical stability, heat resistance and water resistance, thereby effectively improving the service life of the grouting material.
[0015] The present application introduces modified talcum powder, and the introduced talcum powder is ultrafine talcum powder. The smaller the particle size of talcum powder, the larger the specific surface area. On the one hand, talcum powder contains more hydroxyl groups, which react with water to generate hydrogen bonds. The hydroxyl groups cross-link with the gel network in the form of hydrogen bonds to generate a secondary cross-linked network, and the intermolecular force of the gel is strengthened. The force to resist deformation during water loss and shrinkage increases. On the other hand, talcum powder occupies part of the space in the gel body, fills the pores in the gel body, and the pores become smaller, the solid content increases, and the gel body becomes dense, which improves the impermeability coefficient and curing strength of the grouting material. The present application also uses titanate coupling agent and stearic acid to modify the surface of talcum powder. The good synergistic modification effect between the coupling agent and stearic acid effectively overcomes the agglomeration tendency of ultrafine powders, and also better improves the compatibility of modified talcum powder with slurry materials. DETAILED DESCRIPTION
[0016] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0017] Example 1 The preparation method of the modified styrene-acrylic emulsion comprises the following steps: 10 parts by mass of waterborne epoxy emulsion and 5 parts by mass of waterborne epoxy curing agent were uniformly mixed, 45 parts by mass of styrene-acrylic emulsion were added, and the mixture was dispersed at 1000 r / min on a high-speed dispersing shearing machine for 10 minutes to obtain a modified styrene-acrylic emulsion.
[0018] The preparation method of modified talcum powder comprises the following steps: Soaking 3 parts by mass of talc in an acetic acid solution with a pH of 4-5, filtering the solution, and then drying the solution in a vacuum oven at 120° C. to obtain acid-modified talc; The acid-modified talc powder obtained above was added to 0.2 parts by mass of a titanate coupling agent, filtered, and then dried in a vacuum oven at 120° C. to obtain surface-modified talc powder; The surface modified talc powder obtained above was added into a high-speed mixer, stirred at high speed and heated, and when the temperature reached 95-105° C., 0.15 parts by mass of stearic acid was added, stirred at high speed and kept warm for 6 minutes to obtain modified talc powder.
[0019] The preparation method of the acrylic acid salt grouting material for concrete crack anti-seepage repair comprises the following steps: 20 parts by mass of sodium acrylate and 52 parts by mass of water were stirred evenly to prepare a sodium acrylate aqueous solution for use, 25 parts by mass of hydroxyethyl acrylate and 1 part by mass of diethanolamine were added to the sodium acrylate aqueous solution, stirred and mixed evenly, to obtain component A; The modified styrene-acrylic emulsion prepared above, 50 parts by mass of water, 2 parts by mass of sodium persulfate and the modified talc prepared above are stirred and uniformly mixed to obtain component B; The component A and the component B prepared above are blended to obtain an acrylate grouting material for anti-seepage repair of concrete cracks.
[0020] Example 2 The preparation method of the modified styrene-acrylic emulsion comprises the following steps: 15 parts by mass of waterborne epoxy emulsion and 8 parts by mass of waterborne epoxy curing agent were uniformly mixed, 45 parts by mass of styrene-acrylic emulsion were added, and dispersed for 10 minutes at 1200 r / min on a high-speed dispersing shearing machine to obtain a modified styrene-acrylic emulsion.
[0021] The components and planting method of the modified talc are the same as those in Example 1.
[0022] In the preparation steps of the acrylate grouting material for concrete crack anti-seepage repair, the modified styrene-acrylic emulsion is replaced with the modified styrene-acrylic emulsion prepared in this embodiment in an equal amount, and the remaining components and preparation steps are the same as those in Example 1.
[0023] Example 3 The preparation method of modified talcum powder comprises the following steps: 4 parts by mass of talc powder were immersed in an acetic acid solution with a pH of 4-5, filtered, and then dried in a vacuum oven at 120° C. to obtain acid-modified talc powder; The acid-modified talc powder obtained above was added to 0.2 parts by mass of a titanate coupling agent, filtered, and then dried in a vacuum oven at 120° C. to obtain surface-modified talc powder; The surface modified talc powder obtained above was added into a high-speed mixer, stirred at high speed and heated, and when the temperature reached 95-105° C., 0.15 parts by mass of stearic acid was added, stirred at high speed and kept warm for 6 minutes to obtain modified talc powder.
[0024] The components and preparation steps of the modified styrene-acrylic emulsion are the same as those in Example 1.
[0025] In the preparation steps of the acrylate grouting material for concrete crack anti-seepage repair, the modified talc powder is replaced with the modified talc powder prepared in this embodiment in an equal amount, and the remaining components and preparation steps are the same as those in Example 1.
[0026] Example 4 The preparation method of the acrylic acid salt grouting material for concrete crack anti-seepage repair comprises the following steps: 25 parts by mass of sodium acrylate and 60 parts by mass of water were stirred evenly to prepare a sodium acrylate aqueous solution for later use, 25 parts by mass of hydroxyethyl acrylate and 2 parts by mass of diethanolamine were added to the sodium acrylate aqueous solution, stirred evenly to obtain component A; The modified styrene-acrylic emulsion prepared in Example 1, 50 parts by mass of water, 2 parts by mass of sodium persulfate and the modified talc prepared in Example 1 were stirred and uniformly mixed to obtain component B; The component A and the component B prepared above are blended to obtain an acrylate grouting material for anti-seepage repair of concrete cracks.
[0027] Comparative Example 1 The preparation of the modified styrene-acrylic emulsion was omitted.
[0028] The components and preparation steps of the modified talc are the same as those in Example 1.
[0029] In the preparation steps of the acrylate grouting material for concrete crack anti-seepage repair, the modified styrene-acrylic emulsion is replaced with an equal amount of styrene-acrylic emulsion, and the remaining components and preparation steps are the same as those in Example 1.
[0030] Comparative Example 2 The components and preparation steps of the modified styrene-acrylic emulsion are the same as those of Example 1.
[0031] The preparation method of modified talcum powder comprises the following steps: Soaking 3 parts by mass of talc in an acetic acid solution with a pH of 4-5, filtering the solution, and then drying the solution in a vacuum oven at 120° C. to obtain acid-modified talc; The acid-modified talc powder obtained above was added to 0.2 parts by mass of a titanate coupling agent, filtered, and then dried in a vacuum oven at 120° C. to obtain surface-modified talc powder.
[0032] In the preparation step of the acrylate grouting material for concrete crack anti-seepage repair, the modified talc powder is replaced by the surface-modified talc powder prepared in this comparative example, and the remaining components and preparation steps are the same as those in Example 1.
[0033] Comparative Example 3 The components and preparation steps of the modified styrene-acrylic emulsion are the same as those of Example 1.
[0034] The preparation method of modified talcum powder comprises the following steps: Soaking 3 parts by mass of talc in an acetic acid solution with a pH of 4-5, filtering the solution, and then drying the solution in a vacuum oven at 120° C. to obtain acid-modified talc; The acid-modified talc powder obtained above was added into a high-speed mixer, stirred at high speed and heated, and when the temperature reached 95-105° C., 0.15 parts by mass of stearic acid was added, stirred at high speed and kept warm for 6 minutes to obtain modified talc powder.
[0035] In the preparation step of the acrylate grouting material for concrete crack anti-seepage repair, the modified talc powder is replaced by the modified talc powder prepared in this comparative example, and the remaining components and preparation steps are the same as those in Example 1.
[0036] Comparative Example 4 The preparation step of the modified styrene-acrylic emulsion was omitted.
[0037] The preparation step of modified talc was omitted.
[0038] In the preparation steps of the acrylate grouting material for concrete crack anti-seepage repair, the modified styrene-acrylic emulsion is replaced with an equal amount of styrene-acrylic emulsion, and the modified talcum powder is replaced with an equal amount of talcum powder. The remaining components and preparation steps are the same as those in Example 1.
[0039] Performance Testing Viscosity test: Viscosity test is carried out in accordance with GB / T10247 standard.
[0040] Compressive strength test of sand consolidation body: The compressive strength test of sand consolidation body is carried out in accordance with the specification of JC / T2037-2010 "Acrylic Acid Solution Grouting Material".
[0041] Gel time test: Use a stopwatch to record the time, starting from the time component A and component B are mixed, and at the same time, use a glass rod to stir the slurry to make it uniform. When the slurry loses fluidity after the reaction, press the stopwatch again, and the stopwatch reading is the gel time.
[0042] Shrinkage test: Place the test sample in a dry environment until the mass of the solidified body no longer decreases, and the ratio of the remaining mass to the initial mass Permeability coefficient test: refer to GB / T50123-2019 (geotechnical test method standard) permeability test method, pour the prepared acrylate grouting material slurry into the ring cutter, let the slurry form a solid in the ring cutter and let it stand for 1 day, then install the ring cutter with the solid into the permeability container, and perform the permeability test according to the variable head permeability test method. The test results are shown in the table below;
[0043] As can be seen from the above table, the acrylate grouting material for concrete crack anti-seepage repair prepared in Examples 1-4 of the present application has very low viscosity, good pourability, fast slurry gel time, large sand-fixing strength, very good waterproof and anti-seepage effect, and is not prone to shrinkage. While in Comparative Example 1, the styrene-acrylic emulsion is not modified, and the anti-drying shrinkage performance and anti-seepage performance of the grouting material obtained are significantly reduced. In Comparative Examples 2 and 3, only talcum powder is modified with a coupling agent or stearic acid, and the anti-drying shrinkage performance and the strength of the sand-fixing body of the grouting material obtained are reduced. In Comparative Example 4, the styrene-acrylic emulsion and talcum powder added are not modified, and the various properties of the grouting material obtained are all poor. It is shown that the present application will be a grouting material prepared by mixing and polymerizing the B component containing modified styrene-acrylic emulsion and modified talcum powder with the A component containing acrylate, which improves the anti-seepage performance, anti-drying shrinkage performance and service life of the acrylate grouting material.
[0044] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A method for preparing an acrylic acid salt grouting material for concrete crack anti-seepage repair, characterized in that: The method comprises at least the following preparation steps: Mix 15-25 parts by weight of acrylate and 50-60 parts by weight of water, add 20-30 parts by weight of a crosslinking agent and 0.5-2 parts by weight of an accelerator and disperse them evenly to obtain component A; Disperse 50-60 parts by weight of modified styrene-acrylic emulsion, 40-50 parts by weight of water, 1-3 parts by weight of initiator, and 1-5 parts by weight of modified talc powder to obtain component B; The component A and the component B are blended to obtain an acrylate grouting material.
2. The method for preparing an acrylic acid salt grouting material for concrete crack anti-seepage repair according to claim 1, characterized in that: The preparation method of the modified styrene-acrylic emulsion comprises the following steps: The water-based epoxy emulsion and the curing agent are evenly mixed, and the styrene-acrylic emulsion is added, and dispersed for 5-10 minutes at a high-speed dispersion shearing machine of 1000-1500 r / min to obtain a modified styrene-acrylic emulsion.
3. The method for preparing an acrylic acid salt grouting material for concrete crack anti-seepage repair according to claim 2, characterized in that: The curing agent is an aziridine cross-linking agent, and the mass ratio of the waterborne epoxy resin, the curing agent and the styrene-acrylic emulsion is 1:0.5-3:1-6.
4. The method for preparing an acrylic acid salt grouting material for concrete crack anti-seepage repair according to claim 1, characterized in that: The preparation method of the modified talcum powder comprises the following steps: The talc powder is soaked in an acetic acid solution with a pH of 4-5, filtered, and then dried in a vacuum oven at 110-130° C. to obtain an acid-modified talc powder; The acid-modified talc powder is added to a titanate coupling agent, filtered, and then dried in a vacuum oven at 110-130° C. to obtain a surface-modified talc powder; The surface modified talc powder is added into a high-speed mixer, stirred at high speed and heated, and when the temperature reaches 95-105° C., stearic acid is added, stirred at high speed and kept warm for 6-10 minutes to obtain modified talc powder.
5. The method for preparing an acrylic acid salt grouting material for concrete crack anti-seepage repair according to claim 4, characterized in that: The particle size of the talc powder is 4-10 μm, the mass ratio of the acid-modified talc powder to the titanate coupling agent is 1:0.05-0.2, and the mass ratio of the surface-modified talc powder to the stearic acid is 1:0.05-0.
1.
6. The method for preparing an acrylate grouting material for concrete crack anti-seepage repair according to claim 1, characterized in that: The acrylate is any one or more mixtures of calcium acrylate, sodium acrylate or magnesium acrylate, and the crosslinking agent is any one or more mixtures of polyethylene glycol allyl ether, polyethylene glycol acrylate, hydroxyethyl acrylate or hydroxyethyl methacrylate.
7. The method for preparing an acrylate grouting material for concrete crack anti-seepage repair according to claim 1, characterized in that: The accelerator is a mixture of any one or more of triethanolamine, diethanolamine, ferrous sulfate or sodium thiosulfate, and the initiator is a mixture of any one or more of potassium persulfate, ammonium persulfate, sodium persulfate or methyl ethyl ketone peroxide.
8. An acrylate grouting material for concrete crack anti-seepage repair, characterized in that: Prepared by the preparation method described in any one of claims 1 to 7.